Assessing visual fields for driving in patients with paracentral scotomata. Issue 2 (25th October 2007) - Chisholm, C M; Rauscher, F G; Crabb, D C; Davies, L N; Dunne, M C; Edgar, D F; Harlow, J A; James-Galton, M; Petzold, A; Plant, G T; Viswanathan, A C; Underwood, G J; et al.
Abstract : Background: The binocular Esterman visual field test (EVFT) is the current visual field test for driving in the UK. Merging of monocular field tests (Integrated Visual Field, IVF) has been proposed as an alternative for glaucoma patients. Aims: To examine the level of agreement between the EVFT and IVF for patients with binocular paracentral scotomata, caused by either ophthalmological or neurological conditions, and to compare outcomes with useful field of view (UFOV) performance, a test of visual attention thought to be important in driving. Methods: 60 patients with binocular paracentral scotomata but normal visual acuity (VA) were recruited prospectively. Subjects completed and were classified as "pass" or "fail" for the EVFT, IVF and UFOV. Results: Good agreement occurred between the EVFT and IVF in classifying subjects as "pass" or "fail" (kappa = 0.84). Classifications disagreed for four subjects with paracentral scotomata of neurological origin (three "passed" IVF yet "failed" EVFT). Mean UFOV scores did not differ between those who "passed" and those who "failed" both visual field tests (p = 0.11). Agreement between the visual field tests and UFOV was limited (EVFT kappa = 0.22, IVF kappa 0.32). Conclusions: Although the IVF and EVFT agree well in classifying visual fields with regard to legal fitness to drive in the UK, the IVF "passes" some individuals currently classed as unfit to drive due to paracentral scotomata of non-glaucomatous origin. The suitability of the UFOV for assessing crash risk in those with visual field loss is questionable.